Breaking Through the Calcified Neoatherosclerosis - Han Bing, Chow; Tuen, Muen (Elsevier Biomedical, 2025)
CLINICAL INFORMATION Relevant Clinical History and Physical Exam. We report a 62-year-old gentleman with history of hypertension, diabetes mellitus, dyslipidemia, and history of PTCA to LAD and RCA with DES in 1997. He underwent a computed tomography coronary angiography (CTCA) examination for stable angina which revealed severe in stent restenosis with multiple calcified plaques. Guideline directed medical therapies were optimized. After family conference for mode of revascularization, committed to high-risk percutaneous coronary intervention (PCI) approach.